The Development of Short Story Writing Teaching Materials to Improve Student's Writing Skills: A Metaphorming Approach - Yati Suwartini; Ninuk Lustyantie; Muchlas Suseno; Yetti Supriyati (International Journal of Instruction, 2023)
Innovative teaching materials for short story writing are required to enhance students' writing skills. This study proposes the use of the metaphorming approach in developing teaching material for short story writing. This study is a Research and Development (R&D) which used the ADDIE model that consists of five stages, including analysis, design, development, implementation, and evaluation. Data was collected through interviews, tests, questionnaires, and observations at the junior high school level. The design of the teaching materials was integrated with metaphorming principles. Furthermore, the validation process of the design involved experts in metaphorming, instructional design, and linguistics. Thevalidation included three aspects, content, layout, and language. At the implementation stage, teaching material was implemented in the learning to examine its effectiveness in enhancing students' writing skills. A statistical test was carried out to investigate the significance of increasing students' writing skills. The ADDIE model was evaluated at the final stage and at each stage to ensure the quality of development. The results showed that the teaching material for short story writing with a metaphorming approach had met the validity and reliability criteria. Furthermore, its implementation in learning improves students' writing skills significantly